2012
DOI: 10.1186/1824-7288-38-35
|View full text |Cite|
|
Sign up to set email alerts
|

The immunopathogenesis of cow’s milk protein allergy (CMPA)

Abstract: The most frequent symptoms among the manifestations of cow milk protein allergy (CMPA) are gastrointestinal. CMPA pathogenesis involves immunological mechanisms with participation of immunocompetent cells and production of immunoglobulin E (IgE). Nevertheless, recent studies have been focused on the description of other forms of CMPA, not-mediated by IgE reactions, mostly involving the T lymphocite immune system. Thus, in this field it is important to note how different kind of cells are involved in the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 84 publications
1
6
0
1
Order By: Relevance
“…Taken together, with our previous experience with milk‐triggered EoE, the present results provide additional insight into the proposed immunopathological mechanisms involved in EoE as a part of the spectrum of cow's milk allergy . Although the exact mechanisms leading to cow's milk allergy have yet to be completely elucidated , they seem to include both IgE‐ and non‐IgE reactions, as well as a third group of manifestations that are unpredictably associated with IgE antibodies (IgE‐associated/cell‐mediated disorders) . IgE‐mediated allergy to CMP, which seems to predominate in infants and children, is characterized by rapidly evolving symptoms (immediate hypersensitivity) that appear within hours or even minutes after contact with the allergen as a consequence of the rapid release of mediators from mast cells and basophils that occurs when IgE associated with mast cells binds with allergenic epitopes situated on milk proteins.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Taken together, with our previous experience with milk‐triggered EoE, the present results provide additional insight into the proposed immunopathological mechanisms involved in EoE as a part of the spectrum of cow's milk allergy . Although the exact mechanisms leading to cow's milk allergy have yet to be completely elucidated , they seem to include both IgE‐ and non‐IgE reactions, as well as a third group of manifestations that are unpredictably associated with IgE antibodies (IgE‐associated/cell‐mediated disorders) . IgE‐mediated allergy to CMP, which seems to predominate in infants and children, is characterized by rapidly evolving symptoms (immediate hypersensitivity) that appear within hours or even minutes after contact with the allergen as a consequence of the rapid release of mediators from mast cells and basophils that occurs when IgE associated with mast cells binds with allergenic epitopes situated on milk proteins.…”
Section: Discussionsupporting
confidence: 67%
“…Allergy to CMP is recognized as a frequent disorder, the consequences of which range from anaphylaxis to various skin diseases and gastrointestinal motility disturbances , especially in pediatric patients. In fact, the immaturity of the digestive enzymatic system and increased permeability of the mucosa have been related with easy passage of undigested proteins, which can cause a primed immune response through Th2 lymphocyte stimulation, cytokine secretion, and IgE production. In contrast, allergy to CMP is a rare condition among adult patients, in whom lactose intolerance is considered the predominant cause of symptoms related to milk consumption .…”
mentioning
confidence: 99%
“…Cow's milk allergy (CMA) is a complex inflammatory disease in which CD4 + T helper (Th) cells play a central role (Giovanna et al 2012). In addition to the general paradigm of Th1/Th2 immune regulation, the current study showed that two additional Th cell subsets, interleukin 17 (IL-17)-producing Th17 cells and regulatory T cells (Treg), were also partially responsible for the development of allergic inflammation (Palomares et al 2010;Zhao et al 2010).…”
Section: Introductionmentioning
confidence: 83%
“…A defect in oral tolerance is thought to be the underlying cause of food allergy (8). A decreased immune response towards foreign antigens, resulting in dysfunction on Treg cellular activity, seems to be the necessary background for both IgE-and non IgE-mediated CMA (9). The increased antigenic load combined with factors such as atopic predisposition, may initiate an abnormal mucosal immune response resulting in chronic enteropathy (10).…”
Section: Discussionmentioning
confidence: 99%